Novel automated fault isolation system on low voltage distribution automation system - Ahmed, Musse Mohamud; Soo, Wai Lian (2013)
This novel automated fault isolation system has been developed and integrated into a new customer side distribution system of 415/240V. The distribution system is based on the Tenaga Nasional Berhad (TNB), the Malaysia's power utility company especially the distribution system. Supervisory Control and Data Acquisition (SCADA), Remote Terminal Unit (RTUs) and power line communication (PLC) system have been used and developed for detecting, fault locating, fault isolating, fault segregating and power restoration in terms of hardware and software. Open loop distribution system is the distribution configuration system used as TNB distribution system. It is the first distribution automation system (DAS) based on fault management research work on customer side substation for operating and controlling between the consumer side system and the substation. Index Terms---New Service Substation, Fault Detection, Fault Isolation, Fault Segregation, Open Loop System and Counter.